Administrative Regulatory Measures in Relation to the Right to a Clean Environment in Iraqi Law - FalehGeneral , Hussam Al-Din (Basra studies journal, 2026)
This paper examines administrative policing (administrative control) as a legal instrument exercised by public authorities in Iraq with the aim of protecting environmental public order and ensuring individuals’ right to enjoy a clean and healthy environment. This right is considered one of the modern fundamental rights that has gained increasing importance at both international and national levels, particularly in light of escalating environmental challenges such as pollution and the depletion of natural resources. The research focuses on explaining the concept and objectives of administrative policing, while clarifying the legal basis of the right to a clean environment in Iraqi legislation, particularly in the 2005 Iraqi Constitution, which recognizes environmental protection as a duty of the State. It also reviews the main administrative regulatory tools adopted by competent authorities, such as environmental regulations and instructions, the licensing system, inspection and monitoring mechanisms, and administrative sanctions such as fines and closure orders. The study analyzes the role of relevant administrative bodies, such as the Ministry of Environment and municipal authorities, in implementing these mechanisms, while highlighting the challenges they face, including weak enforcement, limited environmental awareness, and overlapping institutional competences. The study concludes that the effectiveness of administrative regulatory measures in protecting the environment in Iraq remains limited despite the existence of an acceptable legal framework, due to administrative and legislative constraints. It recommends strengthening oversight mechanisms, developing environmental legislation, activating the role of administrative judiciary, and promoting environmental awareness among citizens.